2004
DOI: 10.1177/1069072704267738
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Barriers to Employment, Coping Efficacy, and Career Search Efficacy in People with Mental Illness

Abstract: The Barriers to Employment and Coping Efficacy Scale (BECES) and the Career Search Efficacy Scale (CSES) were designed to assist people in their work integration process. The BECES was specifically developed for people with mental illness. Although the CSES was not specifically designed for people with mental illness, its items appear relevant for such clients seeking work. This article reports the construct and convergent validities of these two questionnaires as well as the internal consistency pertaining to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
2
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 35 publications
0
28
2
7
Order By: Relevance
“…Similarly, community studies have discovered that work-related self-efficacy significantly predicts work success over time in people with mental illness [e.g., 4,12,13,[22][23][24]37]. Taken together, these findings suggest that interventions targeting maladaptive thoughts (e.g., cognitive behavioral therapy, or CBT) pertinent to work may be helpful adjuncts to current VA vocational services; this notion of utilizing cognitive strategies has also been suggested to help "nonresponder" consumers with mental illness who continue to struggle with employment functioning despite high quality vocational services [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, community studies have discovered that work-related self-efficacy significantly predicts work success over time in people with mental illness [e.g., 4,12,13,[22][23][24]37]. Taken together, these findings suggest that interventions targeting maladaptive thoughts (e.g., cognitive behavioral therapy, or CBT) pertinent to work may be helpful adjuncts to current VA vocational services; this notion of utilizing cognitive strategies has also been suggested to help "nonresponder" consumers with mental illness who continue to struggle with employment functioning despite high quality vocational services [17].…”
Section: Discussionmentioning
confidence: 99%
“…Because no current measures were designed to systematically assess barriers and facilitators to work functioning in Veterans with mental illness, the survey was developed by study investigators based on key factors that have been identified by prior literature examining competitive employment in community samples of people with mental illness [12,13,[19][20][21]26]. Existing measures, including a barriers checklist used with non-Veterans [6] and a Likertstyle survey examining work barriers [12] also influenced the design of the current survey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ce questionnaire comprend plusieurs scores : le nombre total d'obstacles perçus à l'insertion au travail calculé en fonction des réponses aux énoncés de la première question (43 items) ainsi que les dimensions de la deuxième question qui ont émergé d'analyses factorielles effectuées antérieurement : a) Sentiment de compétence/confiance en soi (9 items), b) Facteurs externes (5 items), c) Anxiété/Amotivation (5 items), d) Santé (6 items), e) Ajustements au travail (5 items) et f) Score global du sentiment d'efficacité pour faire face aux obstacles à l'insertion au travail (30 items). Pour ces dimensions, les coefficients de cohérence interne sont satisfaisants, oscillant entre 0,77 et 0,96 (Corbière et al, 2004a).…”
Section: Questionnaires Et Testsunclassified
“…En bref, les scores aux tests cognitifs permettent de prédire le fonctionnement de la personne à travailler un certain nombre d'heures de travail par mois, mais en aucun cas d'évaluer le maintien en emploi en tant que tel. À un niveau psychosocial, certains auteurs (Corbière et al, 2002 ;Corbière et al, 2004a) insistent non seulement sur l'importance d'évaluer systématiquement les obstacles perçus à l'insertion au travail par cette clientèle, mais aussi de mesurer leur sentiment d'efficacité pour les surmonter. Ils ajoutent que ces évaluations peuvent, a posteriori, aider le conseiller en emploi et ses clients à développer des stratégies pour composer avec ces obstacles perçus à l'emploi.…”
unclassified